Use of Deoxycorticosterone Pivalate by Veterinarians: A Western European Survey - Rita Rebocho (MDPI AG, 2021)
This study aims to gather knowledge about the use of deoxycorticosterone pivalate (DOCP) by Western European Veterinarians (WEV) in dogs with typical hypoadrenocorticism. An observational cross-sectional study was conducted using an online survey, translated into four languages and disseminated to veterinary affiliates and mailing lists in six countries of Western Continental Europe. Respondents were tasked to share their therapeutic approach to hypoadrenocorticism, whether they preferred DOCP or fludrocortisone and the specific practical use of DOCP. One-hundred and eighty-four responses were included. Of these, 79.9% indicated that they preferred prescribing DOCP over fludrocortisone as a first-line treatment for mineralocorticoid supplementation. A total of 154 respondents had used DOCP at least once. Eighty percent of those who reported their initial dosage prescribed 2.2 mg/kg. After starting DOCP, 68.2% of the respondents assess electrolytes 10 and 25 days after administration following manufacturer instructions. In stable dogs, electrolytes are monitored quarterly, monthly, semi-annually, and annually by 44.2%, 34.4%, 16.9%, and 4.6% of respondents respectively. When treatment adjustment is required, 53% prefer to reduce dosage while 47% increase the interval between doses. Overall, DOCP is the preferred mineralocorticoid supplementation among WEV. Reported variability underlies the need to investigate the best strategies for DOCP use and therapeutic adjustments.